Paradigma Toleransi Islam Dalam Merespons Kemajemukan Hidup Di Indonesia: (Studi Analisis Pemikiran KH Ahmad Shiddiq) - Yenuri, Ali Ahmad; Islamy, Athoillah; Aziz, Muhammad; Muhandy, Rachmad Surya (POROS ONIM: Jurnal Sosial Keagamaan, 2021)
This library research intends to identify the foundation and pattern of the Islamic tolerance paradigm that is made by KH. Ahmad Shiddiq in responding to life of life in Indonesia. This type of normative-philosophical research uses the theory of analysis in the form of a typology of religious attitudes (exclusivism, inclusivism, pluralism, eclectism, and universalism). The five typology will be used to identify the foundation and pattern of Ahmad Shiddiq’s paradigm about Islamic tolerance. This research data collection technique uses documentation techniques. Data analysis of this study through three stages in the form of data reduction, data presentation, and conclusion. The results of the study concluded that the foundation of the Islamic tolerance paradigm KH. Ahmad Shiddiq in responding to the pluralism of the life of the Indonesian people can be found in the two big ideas that he made, namely the idea of ​​ukhuwah and society. In this case, there is a tendency for the pattern of the Epistemological Exclusivism of KH. Ahmad Shiddiq, namely making the foundation of the Islamic teachings in formulating the idea of ​​ukhuwah in the form of Islamic values ​​of Islamiah, Ukhuwah Watonis, and Ukhuwah Basyariah. Meanwhile, the foundation of Islamic teachings in the idea of ​​society in the form of the value of tasamuh, tawasuth, tawazun, and amar makruf nahi munkar. Whereas in the axiological aspects there is a tendency of KH. Ahmad Shiddiq universalism, which is in the objectivity of the idea of ​​ukhuwah and society in the reality of pluralism in Indonesia through various attitudes. First, the accommodation attitude, in the form of willingness to accommodate a variety of opinions (aspiration) from various parties. Second, selective attitude, which is to sort out which is useful and not useful. Third, integrative attitude, namely the willingness to harmonize, record and balance the variety of individual interests, minority groups and majority.